Thai Entrepreneur and Community-Based Enterprises OTOP Branded Handicraft Export Performance - Vipada Sitabutr; Paitoon Pimdee (My University, 2017)
Thailand’s One Tambon One Product (OTOP) branded handicraft and food export program is expected in 2016 to reach nearly US$3 billion, with products coming from approximately 6,000, five-star-ranked community-based and small–medium enterprises countrywide. This study therefore examined influences of perceived quality, perceived price, trust, and satisfaction on enterprise export performance using the OTOP product brand. Structural equation modeling used LISREL Version 9.1 to conduct a confirmatory factor analysis and test the hypothesized interrelationships on the variables’ effect on export performance. The vast majority of the entrepreneurs selected by simple random sampling either owned or worked in groups that had 50 or fewer employees, which represented 472 of the survey’s 500 respondents, or 94.4%. Additional results indicated a high and positive correlation between perceived quality, perceived price, trust and satisfaction, and export performance, with the most significant factor affecting export performance being customer satisfaction. In addition, perceived quality also has a positive and direct effect on trust as well as on the exporter’s customer satisfaction. Perceived price plays a role as well and has a direct and positive impact on both customer satisfaction and a customer’s trust of the exporter. Perceived quality also affects export performance in a direct and positive way with trust having a direct and positive impact on satisfaction.
Keywords: LISREL; Customer Satisfaction; Export performance; International Business and FDI